PREDICTION OF MULTIAXIAL LOAD FATIGUE LIFE FOR RUBBER BUSHING - YIN Fang; FAN RangLin; FENG ChengCheng; QI SongQiang; ZENG ZhaoSheng (Jixie qiangdu)
The calculation methods of the maximum principal engineering strain,maximum principal logarithmic strain,maximum principal Green-Lagrange strain,and maximum principal Euler strain and octahedron shear strain peak under uniaxial and multiaxial loading stress condition are studied. It is found that the five damage parameters can be calculated only by outputting the deformation gradient tensor of the dangerous area in the finite element analysis. Based on the fatigue crack initiation theory and the fatigue test data of dumbbell rubber test piece,the life prediction models are established by the above five damage parameters,and the accuracy of the five life prediction models is measured by the goodness of fit value. Among them,the life prediction model with octahedron shear strain peak as damage parameter has the best fitting value. The fatigue life prediction model is established based on the fatigue crack growth theory and the crack growth test data of one-sided notch,pure shear specimen. The life prediction model with octahedral shear strain peak as damage parameter and the life prediction model based on crack growth theory were used to predict the life of the same bushing product respectively. It is found that the life prediction model with octahedral shear strain peak as damage parameter has better prediction effect,and the predicted life is near the triple scatter line of the measured life.